"Beginners Are Many But Enders Are Few": How to End a Course Well and Why It Matters. Issue 3 (2nd September 2022) - Stone, Garrett A.; Powell, Gwynn M.; McGuire, Francis A.
Abstract: The last day of a course is often viewed as awkward, abrupt, and even antithetical to a course's aims. More often than not, prime opportunities for reflection, reinforcement, reconciliation, and closure are typically subsumed to administrative tasks and end-of-course exhaustion. This paper summarizes the scant end-of-course literature, reviews the theoretical importance of ending a course well, and highlights a few "tried and true" end-of-course activities. Ending a course well may help students connect the dots, transfer learning, and experience academic and emotional closure, while simultaneously helping faculty refine their teaching and regroup in preparation for future iterations of the course. As leisure and learning experience design experts, leisure scholars are in a prime position to lead out in meaningful end-of-course pedagogy.